Seed dispersal and its implications for silviculture of African mahogany ( Entandrophragma spp.) in undisturbed forest in the Central African Republic - Medjibe, Vincent; Hall, Jefferson S. (Forest ecology and management, 2002)
The study of seed dispersal has received considerable attention in tropical ecology with emphasis placed on its role in the maintenance of species diversity. Since seeds of numerous high-value tropical timber trees are nominally or actively wind dispersed, the subject is also of interest to tropical foresters. In central Africa, up to 70% of harvested timber trees are wind dispersed, including African mahoganies of the genus Entandrophragma. The dual goals of managing many remote areas in central Africa for both biodiversity and timber production values has led to the consideration of low impact logging techniques. In the Central African Republic, increasing light downwind of Entandrophragma has been proposed as a way of increasing regeneration and recruitment of these trees. Mean wind direction at the time of dehiscence of Entandrophragma angolense and Entandrophragma cylindricum was compared with compass orientation of seed shadows for five individuals in mature, undisturbed forest. Mean wind direction was found to be toward the northeast for morning, afternoon, and daily winds and was significantly different from the orientation of seed shadows for all trees. Mean branch direction did not vary significantly from a random pattern, but matched the direction of the seed shadow better than wind direction did. It is concluded that harvesting interventions aimed at increasing light downwind of Entandrophragma will not necessarily benefit seedlings of the species at the study site and further silvicultural research is needed to determine appropriate management interventions, particularly in remote areas of Africa where conservation values are important.